Consumer Satisfaction towards Coca Cola and Pepsi – A study on Specific Region of Punjab - Kaur , Rajwinder; Kaur, Gagandeep (Gyan Management Journal, 2019)
Customer satisfaction is very important for the Company who is producing any kind of product for the  people. Because now a day's customers who are purchasing the products they have huge knowledge of  various other similar products. This study basically focuses on consumer satisfaction towards Coca  Cola and Pepsi. Various objectives were set for this study and for interpretation SPSS and Excel are used.  This  paper  explores the satisfaction  of  customers  regarding these two  beverages  and  results  and  findings are drawn.
Keywords: Customer; Customer Satisfaction; Preference; Knowledge of Consumer